Financial Inclusion : What Have We Learned So Far? What Do We Have to Learn? - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 2020)
The past two decades have seen a rapid increase in interest in financial inclusion, both from policymakers and researchers. This paper surveys the main findings from the literature, documenting the trends over time and gaps that have arisen across regions, income levels, and gender, among others. It points out that structural, as well as policy-related, factors, such as encouraging banking competition or channeling government payments through bank accounts, play an important role, and describes the potential macro and microeconomic benefits that can be derived from greater financial inclusion. It argues that policy should aim to identify and reduce frictions holding back financial inclusion, rather than targeting specific levels of inclusion. Finally, it suggests areas for future research.